2022
DOI: 10.3390/biology11010092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Complete Mitochondrial Genomes of Five Species of Ricaniidae (Hemiptera: Fulgoromorpha) and Phylogenetic Implications

Abstract: Ricaniidae is a relatively small planthopper family with about 69 genera and 442 species worldwide. Members of this family occur throughout the warm temperate and tropical regions. Some species cause devastating damage to major agricultural and economic plants. However, the relationship between Ricaniidae and other families of Fulgoroidea needs to be further explored. The morphological definitions of the two biggest genera, Pochazia Amyot & Serville, 1843 and Ricania Germar, 1818 (the type genus of Ricanii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…4 ). The lowest nucleotide diversity in cox1 is in agreement with observations in most sequenced insect mitogenomes ( Ma et al 2019 , Ge et al 2021 , Li et al 2021 , Zhang et al 2022 ), which presumably accounts for its ability to provide reliable species identification.…”
Section: Resultssupporting
confidence: 82%
“…4 ). The lowest nucleotide diversity in cox1 is in agreement with observations in most sequenced insect mitogenomes ( Ma et al 2019 , Ge et al 2021 , Li et al 2021 , Zhang et al 2022 ), which presumably accounts for its ability to provide reliable species identification.…”
Section: Resultssupporting
confidence: 82%
“…In this study, the majority of PCGs were represented by complete stop codons of TAA or TAG. Specifically, three PCGs (cox2, nad4, cob) exhibited incomplete stop codons of single T. Zhang et al [ 58 ] reported that the incomplete stop codons in some PCGs were a common feature of most species of vertebrates. But we also found that there are differences in the incomplete stop codons between species from distinct taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Pochazia shantungensis (Chou and Lu, 1977) is an insect of the family Ricaniidae within the order Hemiptera, suborder Auchenorrhyncha, infra-order Fulgoromorpha. Its taxonomic placement has been recently reviewed by Stroi nski and Bourgoin (2022), based on morphological analyses, and on a study of the complete mitochondrial genome by Zhang et al (2022). Their conclusions are still provisional, Identity of the pest (Section 3.1) Is the identity of the pest clearly defined, or has it been shown to produce consistent symptoms and to be transmissible?…”
Section: Identity and Taxonomymentioning
confidence: 99%
“…Its taxonomic placement has been recently reviewed by Stroiński and Bourgoin ( 2022 ), based on morphological analyses, and on a study of the complete mitochondrial genome by Zhang et al. ( 2022 ). Their conclusions are still provisional, pending a more complete taxonomic revision of the full group.…”
Section: Pest Categorisationmentioning
confidence: 99%
See 1 more Smart Citation